CHEMISTRY OF POLYFUNCTIONAL MOLECULES .11. FORMATION AND COMPLEX STABILIZATION OF A NEW CHAIN-LIKE PHOSPHAZENE ANION BY CO(II)-ASSISTED OXIDATIVE SCRAMBLING OF [N(PPH2)2]- - Ellermann, J.; Sutter, Jörg; Knoch, Falk; Moll, Matthias (Angewandte Chemie (International Edition in English), 1993)
Cobalt(II) chloride acts as an oxidizing agent toward lithium bis(diphenylphosphino)amide! Surprisingly, in boiling toluene the two components (molar ratio 1:2) form a phosphazene anion with scrambling of the amide, which reacts further with cobalt(II) to give the spirocyclic metallaphosphazene 1.